Improving the budgetary policy of municipalities - A. B. Urusova (Вестник университета)
The subject of the study is financial relations of municipalities in terms of income generation. The purpose of the article is to disclose and justify measures to increase fairness of the distribution of personal income tax by fixing the share of such a tax for the municipality in which the citizen lives but does not work. The research methods are general scientific (analysis, synthesis, deduction, classification, work with sources) and empirical ones (horizontal analysis). The article considers the problem of imbalance of local budgets caused by pendulum migration and, consequently, by outflow of income from municipalities. An information and software solution has been proposed to ensure the fair distribution of part of the personal income tax between municipalities by the place of residence and work of taxpayers. The logical model of the proposed solution and necessary changes in legislation for its implementation are described. The scope of application is the budget system of the Russian Federation, namely the spheres of municipal finance. Further research should be aimed at identifying additional reserves for strengthening the financial autonomy of municipalities. The expected results of the work include improving the financial situation of the population, optimising the budget system and leveling the level of development of municipalities. The importance of the proposed solution for balanced regional development and improving the quality of life of citizens is emphasised.